Synthesis and characterization of MoX2 (X = O, S, Se, Te) and their electrochemical properties - Yeo, Wan Ping (2016)
Supercapacitor (SC) is a type of energy storage systems which has high energy density and power density. Normally, it can divide into two categories, (i) electrical double layer capacitor (EDLC) and (ii) pseudocapacitor (PC). Nowadays, molybdenum dichalcogenides, a type of pseudocapacitive material, has received the attention from researchers due to two-dimensional layered structure morphology which similar to the structure of graphene. This thesis dealt with synthesis and characterization of molybdenum dichalcogenides in their electrochemical properties. The objective of the thesis was to synthesize molybdenum dichalcogenides. Besides, the molybdenum dichalcogenides synthesized were characterized with physico-chemical and electrochemical techniques, using X-ray Diffractometer, Field Emission Scanning Electron Microscope and potentiostat-galvanostat respectively. Molybdenum dichalcogenides were synthesized with hydrothermal method; the precursors were mixed in a sealed Teflon jacket and incubated it with suitable temperature and period. X-ray diffraction (XRD) was used to reveal the information about crystal structures and chemical compositions of molybdenum dichalcogenides; field emission electron scanning microscopy (FESEM) was used to check the morphologies of molybdenum dichalcogenides; electrochemical testing was used to test the electrochemical properties of molybdenum dichalcogenides. There were three types of analyses involved for electrochemical testing, (i) cyclic voltammetry (CV), (ii) charge discharge (CDC) and (iii) electrochemical impedance spectroscopy (EIS). The acquired results showed that molybdenum trioxide (MoO3), molybdenum disulphide (MoS2) and molybdenum diselenide (MoSe2) had been produced using hydrothermal method. Each of the molybdenum dichalcogenides had its own structure. MoO3 possessed nanosheet structure; MoS2 possessed nanorod structure; MoSe2 possessed nanorod and nanoplate structures. From electrochemical testing, MoS2 showed better performance in specific capacitance, energy density and coulombic efficiency, with values 117.65 F/g at 5 mV/s, 1.63 Wh/kg at 0.3 A/g and 98.93% respectively.